Performance of Organic Manures on Growth and Yield of Tomato (Lycopersicon esculentum L.) Under Jatropha Based Alley Cropping System - Kumar, Rajesh; Ramchandra, (Indian Forester, 2021)
Field experiment was conducted to investigate the effect of different organic manures (FYM + Neem cake + Vermicompost) application on growth and yield of tomato (Lycopersicon esculentum L.) under Jatropha based alley cropping system at the forest nursery, School of Forestry and Environment, Sam Higginbottom Institute of Agriculture, Technology and Sciences, Allahabad (U.P.) India. Total of eight treatments including control were replicated three times. The data recording on plant height, number of branches and number of leaves per plant, number of fruit per plant, fruit weight, fruit diameter, fruit yield per plant at different interval 30 days, 60 days, 90 days and 120 days to evaluate the performance of different combination of organic manures on growth and yield of tomato were found to be maximum in T7 [FYM + Neem cake +Vermicompost] followed by T5 [FYM + Vermicompost], T4 [Fym + Neem cake], T6 [Neem + Vermicompost], T3 [Vermicompost] and minimum in T0 (Control) under the jatropha based alley cropping system. Therefore FYM + Neem cake +Vermicompost can be best combination of jatropha trees if tomato is to be planted. Moreover compared to open field cultivation of tomato crops in growth and yield slightly decreased under the jatropha based alley cropping system. This was due to the allelopathic effect of jatropha on tomato. Although growth and yield slightly decreased however tomato cultivation under jatropha based alley cropping system profited by providing biodiesel and tomato crop at the same time period. Ultimately this will help in reaching goals of sustainable agriculture.